Proceedings of the IEEE 2014 Custom Integrated Circuits Conference 2014
DOI: 10.1109/cicc.2014.6946138
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radiation-induced SRAM and logic soft errors from 0.33V to 1.0V in 65nm CMOS

Abstract: This work details a process-portable test chip, fabricated in 65nm CMOS, specifically designed to measure radiation-induced soft error rate (SER) during operation at near-threshold. A variety of SRAM, register file (RF), and digital logic test structures are included that provide a comprehensive assessment of circuit sensitivities to radiation at low V DD . Neutron irradiation measurements of SRAM/RF show a 6.45x increase in SER when V DD is lowered from 1.0V to 0.33V, and a 2.6x increase in multi-bit upsets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…By checking the sensitivity trends in Figure 2, it can also be observed that the SBU sensitivity significantly increases at very low voltages, especially at near-threshold ones, contrarily to that of MCUs. This trend is consistent with the results presented by Pawlowski et al [21], where it can observed that the sensitivity for all types of MCUs barely increased in the range of 0.3V-1.0V.…”
Section: B Discussionsupporting
confidence: 82%
“…By checking the sensitivity trends in Figure 2, it can also be observed that the SBU sensitivity significantly increases at very low voltages, especially at near-threshold ones, contrarily to that of MCUs. This trend is consistent with the results presented by Pawlowski et al [21], where it can observed that the sensitivity for all types of MCUs barely increased in the range of 0.3V-1.0V.…”
Section: B Discussionsupporting
confidence: 82%
“…The charts display all the rounds of reading that were made (in some cases, several rounds were carried out at the same VCC). The experimental data observed for the 90-nm SRAM is consistent with the results presented by Pawlowski et al [18], where it can be observed that the sensitivity for all types of MCUs barely increased in the range of 0.3V-1.0V. It is also consistent with the results obtained in 2015 in another sample of the same memory, presented in our previous work [10].…”
Section: A Sbu/mcu Sensitivitysupporting
confidence: 82%
“…Combinational logic circuits are significantly less susceptible to soft errors and do not pose a concern [18], [14]. We address both single-event upsets (SEUs) and single-event multiple upsets (SEMUs) [19], [17]. While CLEAR can address soft errors in various digital components of a complex System-on-a-Chip (including uncore components [20] and hardware accelerators), a detailed analysis of soft errors in all these components is beyond the scope of this paper.…”
Section: Introduction His Paper Addresses the Cross-layer Resilienmentioning
confidence: 99%
“…Although the soft error rate of an SRAM cell or a flip-flop stays roughly constant or even decreases over technology generations, the system-level soft error rate increases with increased integration [12], [13], [14], [15]. Moreover, soft error rates can increase when lower supply voltages are used to improve energy efficiency [16], [17]. We focus on flip-flop soft errors because design techniques to protect them are generally expensive.…”
mentioning
confidence: 99%
See 1 more Smart Citation